Filtering 'ways of seeing' through their lenses: representations of Antarctic exploration by lesser known Heroic Era photographers. - Millar, PM (2013)
Photographers made a major contribution to the recording of the Heroic Era of Antarctic exploration. By far the best known photographers were the professionals, Herbert Ponting and Frank Hurley, hired to photograph British and Australasian expeditions. But a great number of photographs were also taken on Belgian, German, Swedish, French, Norwegian and Japanese expeditions. These were taken by amateurs, sometimes designated official photographers, often scientists recording their research. Apart from a few Pole-reaching images from the Norwegian expedition, these lesser known expedition photographers and their work seldom feature in the scholarly literature on the Heroic Era, but they, too, have their importance. They played a vital role in the growing understanding and advancement of Antarctic science; they provided visual evidence of their nation's determination to penetrate the polar unknown; and they played a formative role in public perceptions of Antarctic geopolitics. The objective of this study is to collate background information and literature on lesser known Heroic Era photographers and to offer a discursive examination of photographs, assessing their representations of exploration in Antarctica. Photographers' 'ways of seeing' were influenced by their backgrounds and often by the history of their nations' involvement in Arctic exploration. Their representations were shaped within contexts of prevailing polar exploration discourses‚ÄövÑvÆthe race for the South Pole, nationalism, heroic adventure, and scientific investigation. The images they brought back were determined by the nature of their expeditions, whether inherently scientific, nationalist, or adventure-seeking; by the various sponsoring imperatives; and by how their photographic documentation was intended to be used. This study is important because it offers a comparative consideration of photographers of less well known expeditions from a range of nations and cultures, offering new layers of understanding of the forces that drove the ...